Understanding Significance of Non-Government Organizations and Management - Dr. Radhika Kapur, (Indian Journal of Management and Language (IJML), 2024)
The main objective of this research paper is to acquire an efficient understanding of non-government organizations and management. The non-government organizations have one of the primary goals of promoting wellbeing of community members. The individuals are required to make sure the management has to take place in an efficient manner. The individuals, belonging to all positions in the hierarchy are required to be well-informed in terms of different types of job duties and methodologies. These are vital in promoting functioning of non-government organizations in an effective manner. The primary aim is to put into operation the measures, which are facilitating in alleviating different types of social problems of poverty, illiteracy, unemployment, homelessness and crime and violence. As a consequence of being overwhelmed by all these problems, individuals take help and support from non-government organizations. The augmenting of analytical, critical-thinking and problem-solving skills will be facilitating to the individuals on a comprehensive basis. As a consequence, all the members will contribute efficiently in doing well in one’s jobs and generating desired outcomes. Therefore, it is well-understood, non-government organizations have an indispensable role to play in promoting well-being of community members. The main concepts that are taken into account in this research paper are, understanding the significance of non-government organizations and management, measures to be implemented in enhancing functioning of non-government organizations and management and advantages of enhancing functioning of non-government organizations and management.